2010
DOI: 10.1007/s11095-010-0094-x
|View full text |Cite
|
Sign up to set email alerts
|

Particle Size Influences the Immune Response Produced by Hepatitis B Vaccine Formulated in Inhalable Particles

Abstract: HBsAg delivered in PLGA microspheres elicited an increase in immunogenicity, and the magnitude of immune response was more pronounced with smaller particles. Inhalable particles of HBsAg could be a viable approach to needle-free vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 46 publications
(66 reference statements)
3
54
0
1
Order By: Relevance
“…Previous studies on the influence of particle size on the cellular uptake and immune response were carried out with nanoparticulate materials, such as PLGA, [64,65] …”
Section: Synthesis Of the Cnt-based Immunogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on the influence of particle size on the cellular uptake and immune response were carried out with nanoparticulate materials, such as PLGA, [64,65] …”
Section: Synthesis Of the Cnt-based Immunogensmentioning
confidence: 99%
“…[12,13] Triggering an efficient immune response to low-molecular-weight compounds 60 (haptens) is an even more challenging task because they are smaller and lack a peptide structure, so they cannot be presented by MHC II molecules unless they are conjugated to proteins prior to immunization. [14,15] One of the emerging strategies for increasing the efficiency of the phagocytosis step, thereby enhancing the antibody response, is the use of nanomaterials that can increase the size of the antigen 65 and modify its surface properties. Micro/nanoparticles (MPs/NPs) have been shown to be well-suited for increasing the immune response against protein and peptide antigens because the dimensions of particulate systems are comparable to those of microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Initial burst release has been considered as a major drawback of PLGA-based particulate vaccine formulations (27). The pores on the particle surface can reduce the antigen encapsulation (19). Particle porosity is also known to influence the antigen release rate (28).…”
Section: Discussionmentioning
confidence: 99%
“…As our objective was to delineate the effect of particle parameters on PAD4 immunogenicity, we mainly concentrated on particles with a mean diameter in nanometer or up to 10 µm. It has been reported that particles greater than 10 µm induce a low humoral antibody response (19). However, the influence of particle size on immunogenicity was not clearly elucidated from nanometer to 10-µm particle populations (20).…”
Section: The Explored Methods For the Preparation Of Plga Particulatementioning
confidence: 99%
See 1 more Smart Citation